Kinetic study of liquid phase glycerol hydrodeoxygenation under inert conditions over a Cu-based catalyst. Issue 4 (4th July 2018) - Yfanti, V.-L.; Ipsakis, D.; Lemonidou, A. A.
Abstract : The kinetic model of a liquid phase glycerol hydrodeoxygenation-methanol reforming tandem reaction cycle, over a Cu:Zn:Al catalyst. Abstract : The kinetic modeling of glycerol hydrodeoxygenation reaction over a Cu:Zn:Al catalyst in a batch reactor is reported in this study. The reaction proceeds under inert conditions with hydrogen formed in situ via methanol aqueous phase reforming (APR). A Langmuir–Hinshelwood-type kinetic model, which takes into account the competitive adsorption between reactants and reaction products for the same Cu 0 active sites, accurately describes the reaction steps which involve the hydrodeoxygenation of glycerol to 1, 2-propanediol via hydroxyacetone as an intermediate, the hydrogenolysis of glycerol to ethylene glycol and the hydrogen formation via the methanol APR reaction. The estimation of the involved kinetic parameters was based on experimental tests performed at different reaction times (0–75 min) and reaction temperatures (473–543 K). The reactions mainly contributing to the formation of 1, 2-propanediol were identified as the dehydration of glycerol to hydroxyacetone and its subsequent hydrogenation to the target product. The activation energies for glycerol dehydration and hydroxyacetone hydrogenation reactions were calculated to be 87 and 68.4 kJ mol −1, respectively. Regarding hydrogen formation, the low methanol APR reaction rate was attributed to its low adsorption constant value compared to glycerol and reaction-derived products. The validation of the kinetic model was also investigated by applying it to independent tests with varying glycerol (from 1 to 5 wt%) and methanol (from 7 to 30 wt%) initial concentrations, and the results showed that the model describes the combined reaction cycle for different operating conditions better, when the system is in excess of hydrogen formed via methanol APR.